Challenging authenticity: fakes and forgeries in rock music. Issue 2 (May 2019) - Atton, Chris
Abstract: Authenticity is a key concept in the evaluation of rock music by critics and fans. The production of fakes challenges the means by which listeners evaluate the authentic, by questioning central notions of integrity and sincerity. This article examines the nature and motives of faking in recorded music, such as inventing imaginary groups or passing off studio recordings as live performances. In addition to a survey of types of fakes and the motives of those responsible for them, the article presents two case studies, one of the 'fake' American group the Residents, the other of the Unknown Deutschland series of releases, purporting to be hitherto unknown recordings of German rock groups from the 1970s. By examining the critical reception of these cases and taking into account ethical and aesthetic considerations, the article argues that the relationship between the authentic (the 'real') and the inauthentic (the 'fake') is complex. It concludes that, to judge from fans' responses at least, the fake can be judged as possessing cultural value and may even be considered as authentic.